The Element of Unlawful in Corruption (A Study of the Courtâs Decision of Corruption in the District Court Class IA Jayapura) - Rohrohmana, Basir (Papua Law Journal, 2017)
The element of unlawful (UMH â Unsur Melawan Hukum) in the Criminal Act of Corruption in the criminal justice practice shows a varied view between the prosecutor and the judge in making the decision to the defendant. The object of this study is related to the element of unlawful in corruption by using normative juridical method.Â The result shows that there are variations of the view is caused by (1) UMH, both formal and material, especially formal UMH in the criminal act of corruption is always seen as a bestanddeel element that gives character to other elements, with no prove UMH then other elements are considered unnecessary to be proved again, (2) UMH is considered as a stilzwijgend element which views each delict contained in UMH regardless of written or not in the formulation of a criminal article, but this leads to further debate which is necessary or not to be proved by the public prosecutor if UMH is not expressly written (as in article 2 paragraph (1) UUTPK) in the formulation of a criminal article. However, this is channeled by the view that if it is not clearly stated in the criminal article as in article 3 of UUTPK, it can be understood by applying genus-species approach to UMH as meant in article 2 paragraph (1) UUTPK as genus of UMH in TPK, then UMH its species in article 3 of UUTPK is understood from the element of misusing authority, opportunity, and position that existed on the corruptor.